Robot-Assisted Rehabilitation of Ankle Plantar Flexors Spasticity: A 3-Month Study with Proprioceptive Neuromuscular Facilitation - Zhou, Zhihao; Sun, Yao; Wang, Ninghua; Gao, Fan; Wei, Kunlin; Wang, Qining (Frontiers in Neurorobotics, 2016)
In this paper, we aim to investigate the effect of Proprioceptive Neuromuscular Facilitation (PNF) based rehabilitation for ankle plantar flexors spasticity by using a Robotic Ankle-foot Rehabilitation System (RARS). A modified robot-assisted system was proposed and seven post-stroke patients with hemiplegic spastic ankles participated a three-month of robotic PNF training. Their impaired sides were used as the experimental group while their unimpaired sides as the control group. A robotic intervention for the experimental group generally started from a two minutes passive stretching to warm-up or relax the soleus and gastrocnemius muscle and also ended with the same one. Then a PNF training session included 30 trails was activated between them. The rehabilitation trainings were carried out three times a week as an addition of their regular rehabilitation exercise. Passive ankle joint range of motion, resistance torque and stiffness were measured in both ankles before and after the intervention. The changes in Achilles' tendon length, walking speed, and lower limb function were also evaluated by the same physician or physiotherapist for each participant. Biomechanical measurements before interventions showed significant difference between the experimental group and the control group due to ankle spasticity. For the control group, there was no significant difference in the three months with no robotic intervention. But for the experimental group, passive dorsiflexion range of motion increased ($p<0.01$), resistance torque under different dorsiflexion angle levels (0$^{°}$, 10$^{°}$ and 20$^{°}$) decreased ($p<0.05$, $p<0.001$ and $p<0.001$, respectively), quasi-static stiffness under different dorsiflexion angle levels (0$^{°}$, 10$^{°}$ and 20$^{°}$) also decreased ($p<0.01$, $p<0.001$ and $p<0.001$, respectively). Achilles's tendon length shortened ($p<0.01$) while its thickness showed no significant change ($p>0.05$). The robotic rehabilitation also improved the muscle strength ($p<0.01$) and muscle control performance ($p<0.001$). In addition, improvements were observed in clinical and functional measurements, such as Timed Up-and-Go ($p<0.05$), normal walking speed ($p>0.05$) and fast walking speed ($p<0.05$). These results indicated that PNF based robotic intervention could significantly alleviate lower limb spasticity and improve the motor function in chronic stroke participant. The robotic system could potentially be used as an effective tool in post-stroke rehabilitation training.